The Impact of Plant Diversity on Spider Populations in a Tropical Butterfly Conservatory, Tiruchirappalli, South India - Gayathri, M V; Averal, Horne Iona (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Spiders, as crucial predators and biodiversity indicators, significantly influence ecosystem health. This study investigates the intricate relationship between plant diversity and spider communities within distinct habitats of the Tropical Butterfly Conservatory, Tiruchirappalli, India. By classifying spiders based on their hunting strategies, we aim to understand their ecological roles. This research establishes a baseline for the spider fauna within the conservatory, emphasizing the impact of plant life on spider diversity and distribution. Our findings contribute to a comprehensive evaluation of the ecological importance of spiders in this unique ecosystem, providing valuable insights for future conservation and management efforts. By unravelling the complex interplay between plants and spiders, this study underscores the necessity of preserving plant diversity to sustain a robust and balanced spider community.